2016
DOI: 10.1016/j.rmed.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community pharmacists in COPD management: Inhalation technique and medication adherence

Abstract: SummaryBackground: Inhalation technique and medication adherence are highly important for the management of chronic obstructive pulmonary disease (COPD) since they are essential pre-requisites for achieving full therapeutic effect in patients. Community pharmacists are in the best position to deliver services in these two areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…[3][4][5][6][7][8][9] Inhalation therapy is of paramount importance in the treatment of respiratory conditions. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9] Inhalation therapy is of paramount importance in the treatment of respiratory conditions. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,[10][11][12][13] However, problems related to poor adherence and inhaler technique (IT) among respiratory patients are widely and historically reported in the literature and still represent a challenge for healthcare professionals (HCPs) and healthcare systems to date. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers. 18,20,21 Furthermore, the literature suggests that deterioration in technique can occur as early as 1 month after receiving education about IT.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the low adherence observed in this study, individuals in Missouri might benefit from pharmacist interventions previously found to improve adherence, such as guidance on inhaler usage and technique, close monitoring of markers of poor adherence (missed appointments or prescription refills), provision of individualized patient action plans, discussion of issues relating to adherence, and education on its importance. 22,23 The observations in this study highlight several other issues with which community pharmacists could assist: relatively high rates of smoking, obesity, and anxiety and depression. In addition to COPD clinics, community pharmacists might consider interventions related to these potential contributors to low adherence and high symptom burden in COPD.…”
Section: Discussionmentioning
confidence: 68%
“…The results may provide useful information for development of pharmacist interventions to improve adherence and reduce COPD symptom burden; such interventions have previously demonstrated improved outcomes in patients with respiratory diseases. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] However, patient adherence to ICS is shown to be generally poor, [9][10][11][12] and many patients experience problems in achieving and maintaining the correct inhaler device technique. 5,6,[13][14][15] Patient support programs, such as medication management and counseling, have the potential to improve patient's disease control and medication adherence. 16,17 A previous pharmacist intervention study has shown a positive impact on patients' knowledge about asthma and medication.…”
Section: Introductionmentioning
confidence: 99%